Effect of reduced graphene oxide doping on photocatalytic reduction of Cr(VI) and photocatalytic oxidation of tetracycline by ZnAlTi layered double oxides under visible light. (July 2019) - Ye, Jiaer; Liu, Junhong; Huang, Zhujian; Wu, Siying; Dai, Xide; Zhang, Li; Cui, Lihua
Abstract: The existence of Cr(VI) and antibiotics in the environment can form the joint contaminant which can be hazardous to the ecosystem. To deal with this, we have explored a plausible method to remove the Cr(VI) and tetracycline (TC) from water by visible light photocatalysis. In this study, a series of reduced graphene oxide@ZnAlTi layered double oxides (rGO@LDO) composites with different doping ratio of rGO were successfully synthesized, which were applied in photocatalytic reduction of Cr(VI) and oxidation of TC. Graphene acts as an electron donor and it can enhance the adsorption of Cr(VI) and TC on the surface of the composites. It's found that the obtained ZnAlTi-LDO composites doped with rGO have higher photo-responsiveness in the visible region. The best-performing rGO@LDO composite ( i.e., CGL3) exhibited enhanced visible light-driven photocatalytic Cr(VI) reduction, which was about five times higher than those of ZnAlTi-LDO (without adding hole catcher). The rGO@LDO also showed a satisfactory performance for photocatalytic oxidation of TC with the total organic carbon removal of 80%. However, the doping of rGO did not significantly enhance the removal of TC. The experiment of pH effects demonstrated that acidic pH was favorable to photocatalytic reduction of Cr(VI), while neutral pH was favorable to photocatalytic oxidation of TC. The band structure of ZnAlTi-LDO was first identified, and the EVB and E CB of ZnAlTi-LDO are −2.32 and 0.72 V ( vs . RHE). This research provides a feasible method to remove Cr(VI) and tetracycline from water by employing ZnAlTi-LDO doped with rGO as photocatalyst. Graphical abstract: Image 1 Highlights: The band structure of ZnAlTi-LDO is identified for the first time. ZnAlTi-LDO is mainly composed of semiconductor metal oxides and perovskite phase. Doping of graphene can enhance the photocatalytic reduction of Cr(VI) by 5 times. Acidic pH was favorable to photocatalytic reduction of Cr(VI). Neutral pH was favorable to photocatalytic oxidation of tetracycline.